Chlorpyrifos degradation by plant growth-promoting Alcaligenes faecalis bacteria isolated from oil-contaminated soil. Issue 1 (28th November 2020) - Yadav, Udit; Kushwaha, Sumit; Anand, Vandana; Kumar, Sanjeev; Prakash, Om; Singh, Poonam C.
Abstract: Chlorpyrifos (Chlp), one of the major organophosphates is extensively used in agriculture to control pests. With a half-life of 7–120 d, it may persist for up to one year in soil depending on the soil conditions and affect the soil microflora. Chlp degradation by soil microbes proves to be an effective and environment friendly method to remove it from the soil. This study aims to identify and characterize Chlp degrading soil microbes. Total 173 bacteria isolated from different soil samples were screened for Chlp degradation. Characterization of 10 selected samples showed that all the strains produced excessive exo-polysaccharides (EPSs), which positively correlated with the Chlp degradation under in vitro conditions. Among these 10 bacterial strains, the most potent Chlp degrading bacteria was identified to be Alcaligenes faecalis (NBRI OSS2-5) which paired with the Chlp degrading Pseudomonas in the phylogenetic tree. The strain was shown to possess opd gene reported for Chlp degradation. From the study, it was concluded that EPS production may be a common feature of Chlp degrading microbes which may have some role in the Chlp biodegradation process and the pesticide-contaminated fields may not necessarily be the ideal source of isolating pesticide degrading microbes.